A study of Impact of Emotional Intelligence on Academic Performance of Undergraduate Students in Navi Mumbai Region - Rikhi Yadav; Dr. Mona Sinha (The Bioscan, 2025)
This study explores the influence of Emotional Intelligence (EI) on the academic performance of undergraduate students in the Navi Mumbai region. Emotional Intelligence, encompassing self-awareness, self-regulation, motivation, empathy, and social skills, is increasingly recognized as a key factor contributing to academic success. The research involved a sample of undergraduate students from various disciplines, using a standardized EI assessment tool alongside academic performance indicators such as GPA and semester results. Statistical analysis revealed a significant positive correlation between high levels of EI and improved academic outcomes, suggesting that students who effectively manage emotions and interpersonal relationships tend to perform better academically. The findings highlight the importance of integrating emotional learning into higher education frameworks. By fostering emotional intelligence through structured programs and interventions, educational institutions in Navi Mumbai can enhance students’ learning experiences and overall performance. This research contributes to the growing body of evidence supporting EI as a vital component in student development and calls for educational policymakers to consider EI training as part of the undergraduate curriculum. Further studies may explore longitudinal impacts and how specific EI components influence academic achievements over time.